Pengaruh Video Interaktif dan Media Gambar terhadap Kemampuan Merawat Diri pada Anak Tunagrahita - Indah Rosmaya; Suhendar Sulaeman; Nyimas Heny Purwati (Journal of Telenursing (JOTING), 2019)
This study aims to determine the effectiveness of interactive video and image media on the ability to care for mentally retarded children at SKH Negeri 01 Serang Banten. This research is a quasy experimental design with a non equivalent without control group. The results showed that there was a difference in the average ability to care for mentally retarded children before and after being given interactive video intervention (p value = 0.015, ∆ = 6.67), there was a difference in the average ability to care for mentally retarded children before and after being given the intervention of media images. (p value = 0.006, ∆ = 3.23), and there is a difference in the average ability to care for mentally retarded children before and after being given interactive video and image media interventions (p value = 0.003, ∆ = 1.45). In conclusion, the use of interactive video interventions is more effective as a learning medium in improving the self-care ability of children with moderate mental retardation, but it must be supported by complete facilities and infrastructure. Keywords: Children with mental retardation, Self-Care, Image Media, Interactive Video